Efficiency of Detergents against Microbial Biofilm Growth in Kuching, Sarawak - Elexson, Anak Nillian; Sheryl, Melinda; Micky, Anak Vincent; Lesley, Maurice Bilung (OMICS International, 2016)
Biofilms formed on these surfaces are the main cause of contamination in the final product. The attachment of bacteria to food product or the product contact surfaces leads to serious hygienic problems and economic losses due to food spoilage. Detergent is commonly used as cleaning product to mitigate the growth of microbial on the food product surface and in any food supply chain process. In this study, the efficiency of commercial detergent was analyzed against single cell of foodborne pathogens to biofilm form; Klebsiella pneumonia, Bacillus cereus and Staphylococcus aureus. The antibacterial activity of three detergent; Detergent 1, Detergent 2 and Detergent 3, were evaluated by measuring the diameter zone of inhibition using disc diffusion test. S. aureus showed the highest zone inhibition which is 27.67 ± 0.577 mm (mean ± standard deviation) whereas K. pneumonia showed the lowest zone of inhibition which is 19.97 ± 0.577 mm against Detergent 4. Minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) were determined using 96-well microtiter plates. All detergents exhibited inhibitory activity against bacteria tested. D3 showed the lowest MIC and MBC of S. aureus at 0.390 mg/ml and 0.781 mg/ml respectively, whereas K. pneumonia has the highest MIC and MBC at 3.125 mg/ml and 6.25 mg/ml. The studies have been further done to test minimum bactericidal eradication concentration (MBEC) in related to biofilm eradication capacity. The MBEC result showed Detergent 3 could eradicate biofilm of S. aureus at 3.125 mg/ml. Thus, the appropriate detergent can be incorporated into food product surfaces and processing lines to mitigate the biofilm growth that potentially cause disease outbreak in future.